Stability of self-pollinated corn lines to bubble head with artificial infection in Bukovina - Mykulyak, І.; Linska, М.; Каrp, T.; Kozak, G.; Zaplitnyy, Y. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
An assessment of the resistance of self-pollinated corn lines to the action of the pathogen of bubble head in an infectious nursery with artificial infection of the onset.The result of the research was the isolation of the most tolerant to the damage of bubble head samples that will be used in breeding against resistance to this excitator (Ustilago zeae (Beckm.) Unger).